Drosophila RNase Z processes mitochondrial and nuclear pre-tRNA 3' ends in vivo. - Dubrovsky, E.B.; Dubrovskaya, V.A.; Levinger, L.; Schiffer, S.; Marchfelder, A. (Nucleic Acids Research, 2004)
Although correct tRNA 3' ends are crucial for protein biosynthesis, generation of mature tRNA 3' ends in eukaryotes is poorly understood and has so far only been investigated in vitro. We report here for the first time that eukaryotic tRNA 3' end maturation is catalysed by the endonuclease RNase Z in vivo. Silencing of the JhI-1 gene (RNase Z homolog) in vivo with RNAi in Drosophila S2 cultured cells causes accumulation of nuclear and mitochondrial pre-tRNAs, suggesting that JhI-1 encodes both forms of the tRNA 3' endonuclease RNase Z, and establishing its biological role in endonucleolytic tRNA 3' end processing. In addition our data show that in vivo 5' processing of nuclear and mitochondrial pre-tRNAs occurs before 3' processing.